(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Antifungal potentials of nine fungicides and eight plant parts extracts were tested in opposition to Fusarium oxysporum Schlecht. and F. solani (Mart.) Sacc. – the two pathogens, isolated from wilted roots of brinjal plants. Efficiency gradients observed in the present study expressed that Bavistin and Tall were the best inhibiting agent against the in vitro growth of the test pathogenic fungi. Among aqueous extracts of eight plant parts significant inhibition of the growth of the pathogens was observed with Azadiracta indica (leaf), Zingiber officinale (rhizome) and Asparagus racemosus (root) at 20% concentration. Dhaka Univ. J. Biol. Sci. 24(2): 209-213, 2015 (July)